Politeness Strategies Applied by the Characters of The Great Debaters Movie - Rosari, Miwita (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2016)
This research explores politeness strategies used by the characters in The Great Debaters movie. The data used in this research were collected from 166 pages of The Great Debaters movie transcription. The analysis is based on Brown and Levinsonâs politeness strategies and Spolskyâs factors affecting someoneâs politeness in speaking. The research results showed that the characters in The Great Debaters movie applied the types of politeness strategies, namely off-record, baldon-record, positive politeness, and negative politeness. Moreover, the characters alsoÂ revealed the factors affecting the charactersâ politeness in speaking, namelyÂ language style, register and domain, and slang and solidarity. However, the characters did not show language and gender factor in their conversation since they were mostly engaged in the same topic, namely a debate competition.Â DOI: https://doi.org/10.24071/llt.2016.190103